A physiological dose of oral vitamin B-12 improves hematological, biochemical-metabolic indices and peripheral nerve function in B-12 deficient Indian adolescent women - Yajnik, Chittaranjan S. (PLoS One, 2019)
BACKGROUND: Vitamin B-12 deficiency is often considered synonymous with pernicious anemia, a rare condition in which severe malabsorption of the vitamin requires high-dose parenteral treatment. In developing countries such as India, inadequate dietary intake of B-12 due to socio-cultural factors leads to widely prevalent asymptomatic low B-12 status. In this scenario, lower doses of oral B-12 may be effective, safer and more affordable. OBJECTIVE: To examine the effects of oral B-12 treatment at physiological doses on hematological and biochemical indices and peripheral nerve function in B-12 deficient rural Indian adolescent women. METHODS: Thirty-nine women with B-12 deficiency who were excluded from a community based B-12 supplementation trial (Pune Rural Intervention in Young Adolescents (PRIYA)) received oral B-12 2μg/day, either alone (n = 19) or with multiple micronutrients (UNIMAPP formula + 20gm milk powder, n = 20) for 11 months. Hematological indices, nutrients (B-12, folate), metabolites (homocysteine) and peripheral nerve function (SUDOSCAN, Impetomedical, Paris and sensory nerve conduction velocity (NCV) of median and sural nerves) were assessed at baseline and after 11 months of B-12 treatment. RESULTS: Results were similar in the two treatment allocation groups, which were therefore combined. At baseline, all women had B-12 concentration <100pmol/L, 79% were anemic and 33% had macrocytosis, but none had neuropathy. After 11 months of treatment, B-12 levels increased, while folate did not change. The prevalence of anemia fell to 59% and mean corpuscular volume (MCV) and plasma homocysteine concentrations decreased. Sudomotor nerve function in the feet improved by an average of 14.7%, and sensory conduction velocity in median and sural nerves increased by 16.2% and 29.4% respectively. CONCLUSION: We document clinically beneficial effects of supplementation with a physiological dose of oral B-12 in asymptomatic rural Indian adolescent women with very low B-12 status. These findings support a public health approach to tackle the widely prevalent low B-12 status in young Indians.